1988
DOI: 10.1128/jb.170.2.946-953.1988
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin and quinolone action in archaebacteria: evidence for the presence of a DNA gyrase-like enzyme

Abstract: The action of novobiocin and coumermycin (two coumarins which interact with the gyrB subunit of eubacterial DNA gyrase) and ciprofloxacin (a fluoroquinolone which interacts with the gyrA subunit of DNA gyrase) was tested on several archaebacteria, including five methanogens, two halobacteria, and a thermoacidophile. Most strains were sensitive to doses of coumarins (0.02 to 10 Rg/ml) which specifically inhibit DNA gyrase in eubacteria. Ciprofloxacin inhibited growth of the haloalkaliphilic strain Natronobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
4
40
0
2
Order By: Relevance
“…1). Interestingly, we have previously found that plasmids from halophilic archaebacteria-which are mesophiles-are also negatively supercoiled (15,34,35). More recent data go as far as to suggest that these halophilic plasmids are even more negatively supercoiled than eubacterial ones (6).…”
Section: Resultsmentioning
confidence: 98%
“…1). Interestingly, we have previously found that plasmids from halophilic archaebacteria-which are mesophiles-are also negatively supercoiled (15,34,35). More recent data go as far as to suggest that these halophilic plasmids are even more negatively supercoiled than eubacterial ones (6).…”
Section: Resultsmentioning
confidence: 98%
“…A direct comparison between the mode of action of quinolones and epipodophyllotoxins has been hampered by the lack of a living organism sensitive to both drugs. We have previously shown that archeabacteria are sensitive to inhibitors of eukaryotic and eubacterial type II DNA topoisomerase (7,8), a finding that correlates well with the intermediate phylogenetic position of archeabacteria between eukaryotes and 'classical bacteria' or eubacteria (2,9). In this respect, we have demonstrated that ciprofloxacin, novobiocin, and etoposide have a common target in Halobacterium GRB: an archaebacterial type II DNA topoisomerase (10,11).…”
Section: Introductionmentioning
confidence: 88%
“…Cleavage of pGRB-1 plasmid DNA induced by either ciprofloxacin or the antitumoral drug etoposide VP16, produced DNA fragments of identical lengths, indicating that both drugs trap the reaction intermediates between the archaebacterial DNA topoisomerase and pGRB-1 DNA at the same sites (10). It should be noted that among the archaebacteria, the halobacteria are the most sensitive organisms to DNA topoisomerase II inhibitors (7).…”
Section: Introductionmentioning
confidence: 99%
“…The genome contains only one type II topoisomerase of the TopoVI family (Sso0968 and Sso0969) (48). No gyrase genes were detected, although Sulfolobus is novobiocin sensitive (49). Neither reverse gyrase nor TopoVI activity is inhibited by this drug (50,51).…”
Section: Dna Replication and The Cell Cyclementioning
confidence: 99%